Metformin attenuates diabetic osteoporosis by suppressing ferroptosis via the AMPK/Nrf2 pathway - Liu, Yanwei; Fu, Zhaoyu; Wang, Xinyu; Yang, Qifan; Liu, Shun; Zhu, Dong (Frontiers in Pharmacology, 2025)
BackgroundFerroptosis is a critical factor in the impairment of osteoblast function in osteoporosis. Metformin (Met), a biguanide antidiabetic drug, has demonstrated anti-osteoporotic effects and has been confirmed to exert therapeutic benefits in diabetic osteoporosis (DOP). Nevertheless, the underlying mechanisms through which Met affects bone metabolism remain ambiguous.ObjectiveThis study seeks to elucidate the function of Met in DOP and to explore the potential mechanisms through which it mediates treatment effects.MethodsIn vitro, we utilized osteoblasts to explore the impact of Met on osteoblast differentiation and anti-ferroptosis in a high glucose and palmitic acid (HGHF) environment. In vivo, we developed a DOP model utilizing a high-fat diet along with streptozocin injections and evaluated the bone-protective effects of Met through micro-CT and histomorphological analyses.ResultsMet inhibits HGHF-induced ferroptosis in osteoblasts, as indicated by the elevation of ferroptosis-protective proteins (GPX4, FTH1, and SLAC7A11), along with decreased lipid peroxidation and ferrous ion levels. Furthermore, Met augmented the levels of osteogenic markers (RUNX2 and COL1A1) and enhanced alkaline phosphatase activity in osteoblasts under HGHF conditions. Mechanistic investigations revealed that Met activates the AMPK/Nrf2 pathway, effectively preventing ferroptosis progression. Additionally, in vivo results demonstrated Met alleviates bone loss and microstructural deterioration in DOP rats.ConclusionMet can activate the AMPK/Nrf2 pathway to prevent ferroptosis, thereby protecting against DOP.